The plasma free fraction of 25-hydroxyvitamin D3 is not strongly associated with 25-hydroxyvitamin D3 clearance in kidney disease patients and controls. Issue 226 (February 2023) - Best, Cora M.; Thummel, Kenneth E.; Hsu, Simon; Lin, Yvonne; Zelnick, Leila R.; Kestenbaum, Bryan; Kushnir, Mark M.; de Boer, Ian H.; Hoofnagle, Andrew N.
Abstract: Circulating 25-hydroxyvitamin D [25(OH)D] concentration is used to monitor vitamin D status. Plasma protein binding may influence the 25(OH)D dose-response to vitamin D treatment through a direct relationship between the plasma unbound ("free") fraction and clearance of 25(OH)D. We previously evaluated 25(OH)D3 clearance in relation to kidney function using intravenous administration of deuterium labeled 25(OH)D3 . In this follow up study, we determined the free fraction of 25(OH)D3 in plasma ( i.e., percent free 25(OH)D3 ) and the serum concentration and haplotype of vitamin D binding protein in these participants. We hypothesized that the percent free 25(OH)D3 would be positively associated with 25(OH)D3 clearance and would mediate associations between clearance and vitamin D binding protein ( GC ) haplotypes. Participants were mean (SD) age 64 (10) years and included 42 individuals with normal kidney function (controls), 24 individuals with chronic kidney disease, and 19 individuals with kidney failure on hemodialysis. Free plasma 25(OH)D2 and 25(OH)D3 concentrations were quantified with a new liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. Because there is no reference measurement procedure for free 25(OH)D, we compared the new method with a widely-used predictive equation and a commercial immunoassay. The percent free 25(OH)D3 determined by predictive equation was weakly associated with 25(OH)D3 clearance (R = 0.27; P = 0.01). However, this association was absent when percent free 25(OH)D3 was determined using LC-MS/MS-measured free and total 25(OH)D3 concentrations. Method comparison uncovered a negative bias in immunoassay-measured free 25(OH)D concentrations among participants with kidney failure, so immunoassay results were not used to evaluate the association between percent free 25(OH)D3 and clearance. GC2 haplotype carriage was associated with 25(OH)D3 clearance. Among individuals with 2 relative to no GC2 alleles, clearance was 87 (95% CI: 15–158) mL/d greater. However, in contrast with the literature, GC2 carriage was not significantly related to DBP concentration or the percent free 25(OH)D3 (either predicted or measured). In conclusion, the free fraction of 25(OH)D3 is not strongly associated with 25(OH)D3 clearance but may explain small differences in clearance according to GC haplotype. Highlights: We assessed systemic clearance of 25(OH)D3 in humans. Clearance of 25(OH)D3 varied according to vitamin D binding protein ( GC ) haplotype. We employed a novel liquid chromatography-mass spectrometry assay for free 25(OH)D. We observed a negative bias in immunoassay-measured free 25(OH)D concentrations.